Exploring Associations Between a Maternal Nutrition+Exercise Intervention in Pregnancy and Infant Growth and Body Composition - Dempsey, Kendra (My University, 2020)
Background: Pregnancy lifestyle interventions may effectively mediate gestational weight gain and adverse pregnancy outcomes. Whether maternal diet and exercise in pregnancy also benefits offspring body size and composition in infancy is not widely investigated. Further, adherence to interventions in longitudinal studies is often overlooked. Objectives: 1) Determine the effects of a nutrition+exercise intervention compared with standard prenatal care throughout pregnancy on infant anthropometry and body composition 2) Compare the dietary practices between intervention and control groups 3) Create an algorithm to assess intervention adherence Study Design: Maternal diet and physical activity were collected from a subset of women at 12-17, 26-28, 36-38 weeks gestation while enrolled in the Be Healthy in Pregnancy randomized controlled trial. Infant birth size was obtained from hospital records, and anthropometry and body composition outcomes were measured at six months postpartum. Percentile values for anthropometric measures were obtained using population reference growth standards. Diet quality was assessed through food frequency questionnaire, and a novel adherence algorithm was created using step counts from an accelerometer and three-day diet record. Results: For 183 participants of mean age 31 ± 4 years and BMI 25.3 ± 4.7 kg/m2 , infant anthropometry and body composition at birth and six months were similar between intervention and control groups with the exception that intervention infants had significantly higher birth length and a higher proportion categorized above the 97th percentile for reference length measures. In the analysis of healthy dietary practices (N=111) intervention and control participants had similar scores at baseline but only intervention participants improved and maintained their dietary practice scores in mid and late pregnancy. Application of the adherence score incorporating diet and step counts demonstrated increased adherence to the intervention in mid-pregnancy in intervention participants, but this level of adherence was not maintained through the end of pregnancy. Conclusion: In a healthy pregnant cohort, a lifestyle intervention did not significantly impact infant anthropometry or body composition and most measures were within appropriate reference ranges for age and sex. The novel algorithm to measure intervention adherence demonstrated inconsistent compliance across pregnancy in intervention participants, potentially contributing to null findings.
Keywords: nutrition; exercise; pregnancy; body composition; pediatrics; diet; intervention